Performing Anaphora in Modern Greek: A Neo-Gricean Pragmatic Analysis - Chiou, Michael (Research in Language, 2013)
The paper addresses the problem of interpreting anaphoric NPs in Modern Greek. It includes a proposal of a novel analysis based on the systematic interaction of the neo- Gricean pragmatic principles of communication, which provides a neat and elegant approach to NP-anaphora resolution. The findings of this study provide evidence for an account of NP-anaphora in terms of the division of labour between syntax and pragmatics and more accurately in terms of the systematic interaction of the neo-Gricean pragmatic principles.